María Zambrano: a woman, a republican and a philosopher in exile - PALOMAR GALDÓN, PATRICIA (Journal of Education Culture and Society, 2020)
The subject of this presentation is an attempt to understand the concept of exile in terms of the works of Spanish philosopher María Zambrano, a woman who left her country after the Spanish civil war and lived the life of an exile. This work focuses on the difficulties enco-untered by thinkers when they try to reflect on the experience of exile, and it aims to bring Zambrano’s thought on exile closer to her main philosophical concepts.